The psychopathology of the revolution in Spain (1880-1923): Psychiatric discourses and professional interests - Campos, Ricardo (Historia y Política, 2026)
The article examines how the clinical gaze of Spanish psychiatrists was shaped in relation to social problems and revolutionary movements in Spain between 1880 and 1923. To this end, it considers how professional concerns and strategies influenced their discourses and perspectives on social protest. In the first part, it explains why, until the 1910s, they analysed social problems and revolutions exclusively from an individual clinical perspective, setting aside collective psychopathological interpretations. It shows how the weakness of nineteenth-century psychiatry and the State’s lack of interest in its proposals led psychiatrists to focus their efforts at professional legitimisation on psychiatric expert reports, concentrating their attention on clinical issues and individual behaviour, particularly in the case of anarchists and regicides. In the second part, it examines how, from 1910 onwards, as a result of the country’s situation and the growing role of medicine in its regeneration, psychiatrists progressively incorporated a collective psychopathological view of revolutionary movements and their leaders, pathologising social and political protest. The sources used include publications in specialised journals, articles in the general press, lectures, psychiatric expert reports, and treatises on psychiatry and criminology.